Lectura eficiente de un texto literario narrativo a partir de la metacognición en español como lengua no materna - Aznar Juan, María Luisa; Gamazo Carretero, Elena (Huarte de San Juan. Filología y Didáctica de la Lengua, 2022)
Reading comprehension assessment for students is not limited to the question-and-answer strategies. In order to achieve an effective reading comprehension (RC) it is paramount to activate the conscious awareness and learning control strategies. In this context, literary texts are not only a source of linguistic and cultural knowledge, but they are also an optimal framework for communicative situation representation. This study focuses on the RC development in literary texts using metacognitive strategies for the Spanish as a foreign language (ELE) classroom. Our aim is to present the findings of a research carried out with C1 level university students and showcase its connection with the results of a previously conducted research with B2 level students in the same context. The used methodology entails a classroom-based research, both applied and descriptive, completed through a simple qualitative and quantitative data analysis.